Hubungan Pengetahuan Wanita Usia Subur (WUS) dengan Penggunaan Kontrasepsi IUD di Puskesmas Pagar Merbau Kec. Pagar Merbau Kab.Deli Serdang Tahun 2023 - Ketut Juliana; Kamelia Sinaga; Imran Saputra Surbakti; Asnita Sinaga; Rahmah Rahmah (Jurnal Siti Rufaidah, 2024)
Family Planning (KB) is an effort to help individuals or married couples plan the number and spacing of births as desired, and avoid unwanted pregnancies. This program also aims to regulate the time of birth based on the age of the couple and family conditions. This study aims to analyze the relationship between the level of knowledge of Women of Childbearing Age (WUS) and the use of IUD contraception at the Pagar Merbau Health Center, Pagar Merbau District, Deli Serdang Regency in 2023. The type of research is Descriptive Correlation with a cross-sectional design, the research sample was 45 people, the sampling technique used the Total Sampling method. the results of the study showed that Based on statistical analysis using the chi-square test, a significant relationship was found between the level of knowledge of WUS and the use of IUD contraception at the Pagar Merbau Health Center, Pagar Merbau District, Deli Serdang Regency in 2023, with a p-value of 0.006 (p-value <0.05). The more knowledge a person has about something, the higher the level of knowledge of that person. One of the factors that influences health behavior is the predisposition factor which is manifested in knowledge, where a person's knowledge greatly influences the actions that will be carried out.